Correction: Influences of atmospherics on customer satisfaction and behavioural intentions in the restaurant industry: Evidence from an emerging economy. - Mananage Shanika Hansini Rathnasiri; Pawan Kumar; Bindu Aggarwal; Kiran Nair; Narayanage Jayantha Dewasiri (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0319948.].